Inclusive dijet cross sections in neutral current deep inelastic scattering at HERA - Abramowicz, H.; Abt, I.; Adamczyk, L.; Adamus, M.; Aggarwal, R.; Antonelli, S.; Antonioli, P.; Antonov, A.; Arneodo, M.; Aushev, V.; Aushev, Y.; Bachynska, O.; et al. (Springer Verlag (Germany), 2010)
Single- and double-differential inclusive dijet cross sections in neutral current deep inelastic ep scattering have been measured with the ZEUS detector using an integrated luminosity of 374 pb(-1). The measurement was performed at large values of the photon virtuality, Q (2), between 125 and 20 000 GeV2. The jets were reconstructed with the k (T) cluster algorithm in the Breit reference frame and selected by requiring their transverse energies in the Breit frame, E-jet (T,B), to be larger than 8 GeV. In addition, the invariant mass of the dijet system, M-jj,M- was required to be greater than 20 GeV. The cross sections are described by the predictions of next-to-leading-order QCD.